Isolation of a cotton NADP(H) oxidase homologue induced by drought stress - Nepomuceno, Alexandre Lima; Stewart, James MCD; Oosterhuis, Derrick; Turley, Rickie; Neumaier, Norman; Faria, José Renato Bouças (Pesquisa Agropecuaria Brasileira, 2000)
The aim of this study was to identify and isolate genes that are differentially expressed in four selected cotton (Gossypium hirsutum L.) genotypes contrasting according to their tolerance to water deficit. The genotypes studied were Siokra L-23, Stoneville 506, CS 50 and T-1521. Physiological, morphological and developmental changes that confer drought tolerance in plants must have a molecular genetic basis. To identify and isolate the genes, the mRNA Differential Display (DD) technique was used. Messenger RNAs differentially expressed during water deficit were identified, isolated, cloned and sequenced. The cloned transcript A12B15-5, a NADP(H) oxidase homologue, was up regulated only during the water deficit stress and only in Siokra L-23, a drought tolerant genotype. Ribonuclease protection assay confirmed that transcription.